Achieving high quality electron beam with ultralow energy spread from mismatched plasma channels - Jiabao Guan; Qiannan Lei; Jianhua Zhong; Lanxin Liu; Yuancun Nie; Guoxing Xia; Jike Wang (Scientific Reports)
Abstract Intense electric fields generated by laser plasma wakefield accelerators can rapidly accelerate electrons to high energies over short distances, potentially reducing both the length and cost of accelerator facilities significantly. However, the electron beams produced often exhibit substantial energy spreads, which imposes significant constraints on their broader applicability. We propose a novel method for reducing energy spread by utilizing periodic changes in the acceleration field slope induced by mismatched plasma channels, allowing for periodic compensation of the energy spread. Simulations of a 1 GeV, 10 pC electron accelerator demonstrate that this method can reduce the energy spread of the electron beam to 0.17%, while effectively preserving other beam quality parameters. This approach is approaching the state-of-the-art in laser plasma wakefield accelerators and holds promise for applications in free electron lasers and synchrotron radiation source injectors.